Batman returns - Burton, Tim, 1958-; Waters, Daniel; Keaton, Michael, 1951-; DeVito, Danny; Pfeiffer, Michelle, 1957-; Warner Bros; Warner Home Video (Firm) (Burbank, CA : Warner Home Video, 2005)
The Caped Crusader returns to do battle with Catwoman and the Penguin.
Based on characters created by Bob Kane and published by DC Comics.
Sequel to Batman (1989).
Originally released as a motion picture in 1992.
Features: "The cinematic saga of Batman, shadows of the bat pt. 4," "Beyond Batman documentary gallery," heroes and villains profile galleries, interviews: "The bat, The cat, and the penguin," music video: "Face to face" by Souixsie and the Bashees.
Director of photography, Stefan Czapsky ; production designer, Bo Welch ; film editor, Chris Levenzon ; music, Danny Elfman.
Michael Keaton, Danny DeVito, Michelle Pfeiffer, Christopher Walken, Michael Gough, Pat Hingle, Michael Murphy.
Keywords: Batman (Fictitious character) -- Drama; Adventure films; Film sequels; Video recordings for the hearing impaired; Fiction films; Feature films